2017
DOI: 10.1002/phar.1960
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Absorption of Dolutegravir and Tenofovir Disoproxil Fumarate, But Not Emtricitabine, in anHIV‐Infected Patient Following Oral and Jejunostomy‐Tube Administration

Abstract: The use of enteral feeding tubes to administer antiretroviral medication administration is necessary in certain patients with human immunodeficiency virus (HIV) infection. However, adequacy of drug exposures after these administration routes are largely unknown, making dosing recommendations and the attainment of viral suppression challenging in this patient population. This report describes a patient with advanced HIV infection and a complicated medical history, including long-term intractable nausea/vomiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The DTG C t of 820 ng/ml following the higher 50 mg twice daily dosing was similar to the reference of 830 ng/ml with 50 mg daily dosing. Another case report in a CI-PLWH found that DTG exposure was similar when administered oral versus jejunostomy tube, but the AUC exposure was 76% and 75% lower compared with the literature, respectively [17]. Similar to the current report, all previous reports describe maintenance of viral suppression with altered DTG administration [1619].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The DTG C t of 820 ng/ml following the higher 50 mg twice daily dosing was similar to the reference of 830 ng/ml with 50 mg daily dosing. Another case report in a CI-PLWH found that DTG exposure was similar when administered oral versus jejunostomy tube, but the AUC exposure was 76% and 75% lower compared with the literature, respectively [17]. Similar to the current report, all previous reports describe maintenance of viral suppression with altered DTG administration [1619].…”
Section: Discussionsupporting
confidence: 82%
“…Specifically, the DTG AUC 0–t and C max was 26% and 30% higher compared with references [15]. Few case reports assess crushed DTG in PLWH [1619]. One case report described a CI-PLWH where DTG was increased to 50 mg twice daily given crushed via gastrostomy tube.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, Brooks et al. 2 observed lower levels of DTG when administered once-daily via jejunostomy tube. Altered bioavailability with administration of crushed combination tablets containing either DTG or tenofovir alafenamide (TAF) has also been reported.…”
Section: Introductionmentioning
confidence: 86%
“…The data in this area is limited but emerging. [61][62][63] Providers should consult with their clinical pharmacists and the manufacturer, or perform a literature search for the most recent data. The University of Toronto also maintains a summary of data on their website, which may be a useful resource (https://hivclinic.ca/).…”
Section: Optimizing Antiretroviral Therapy In Setting Of Virologic Sumentioning
confidence: 99%